2020
DOI: 10.1080/13032917.2020.1851093
|View full text |Cite
|
Sign up to set email alerts
|

Customer preferences and self-service technologies:hospitality in the pandemic context

Abstract: Given the fact that tourism is one of the most affected sectors by the Covid-19 pandemic, the main objective of this study was to analyze important aspects inherent to the current use of Self-Service Technologies (SSTs) in the hospitality sector. The results of this study are based on a questionnaire that was applied in May 2020, and indicate that the use of SSTs can be an important asset for the hospitality industry during the pandemic, including developing countries contexts. The relevance of this asset was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…social distancing, health risks and perceptions) on the tourists' decision-making and behavior. Many papers extend their discussions by also reflecting on the subsequent consequences of the ‘new’ tourists' behaviors in terms of how tourism destinations and organizations should respond specifically in terms of: 1) re-developing and re-position their offerings ( Bae & Chang, 2021 ; Jarratt, 2020 ; Sánchez-Cañizares, Cabeza-Ramírez, Muñoz-Fernández, & Fuentes-García, 2020 ; Stankov, Filimonau, & Vujičić, 2020 ) and, 2) using technologies for digitizing operations and offerings to provide and monitor a safe environment of touchless/contactless tourism experiences ( Christou, Simillidou, & Stylianou, 2020 ; Lau, 2020 , Oliveira, Maia, Fonseca, & Moraes, 2021 ). Researchers have also indicated the critical role that technology can play in helping tourism organizations to provide a safe service environment, e.g.…”
Section: Analysis and Discussion Of The Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…social distancing, health risks and perceptions) on the tourists' decision-making and behavior. Many papers extend their discussions by also reflecting on the subsequent consequences of the ‘new’ tourists' behaviors in terms of how tourism destinations and organizations should respond specifically in terms of: 1) re-developing and re-position their offerings ( Bae & Chang, 2021 ; Jarratt, 2020 ; Sánchez-Cañizares, Cabeza-Ramírez, Muñoz-Fernández, & Fuentes-García, 2020 ; Stankov, Filimonau, & Vujičić, 2020 ) and, 2) using technologies for digitizing operations and offerings to provide and monitor a safe environment of touchless/contactless tourism experiences ( Christou, Simillidou, & Stylianou, 2020 ; Lau, 2020 , Oliveira, Maia, Fonseca, & Moraes, 2021 ). Researchers have also indicated the critical role that technology can play in helping tourism organizations to provide a safe service environment, e.g.…”
Section: Analysis and Discussion Of The Findingsmentioning
confidence: 99%
“…virtual tourism can substitute visitation and be detrimental in jobs/income generation at the destination, but it can also contribute to environmental responsibility, Beck, Rainoldi, & Egger, 2019 ). Moreover, studies have focused on investigating technology applications in tourism and they have failed to explore the impact of technologies from the tourism demand perspective and/or the environment (for example examining the technology impacts on tourists' perceived risk, travel intentions, behavior) ( Christou et al, 2020 ; Lau, 2020 ; Oliveira et al, 2021 ).…”
Section: Analysis and Discussion Of The Findingsmentioning
confidence: 99%
“…The opinion that SSTs functionally benefit the customer is reflected in the literature, and is supported by the convenience, control, and access to lower price (Cetto et al, 2015). The findings of this study introduce the forced usage and meeting needs which counter the established utilitarian view of SSTs in the literature (Oliveira et al, 2021;Park et al, 2021). These findings explain the various, and sometimes contradictory, reasons at play, ranging from using SSTs to accommodate the client (motivated by convenience) to using SSTs to accommodate the service provider (forced usage motivation).…”
Section: Discussionmentioning
confidence: 58%
“…In the research that has been done, various motivations for use and the accompanying gratifications sought by customers have been identified. These include things like convenience (Collier & Kimes, 2013;Lee & Yang, 2013), access to the service around the clock (Oliveira et al, 2021), control (Shiwen et al, 2022), time and money savings (Palau-Saumell et al, 2019), enjoyment or fun (Collier & Barnes, 2015;Meuter et al, 2000). This study has found that the motivations of convenience and access to lower price have emerged as leading service outcomes that help customers achieve more efficiency in their lives by managing a budget and coping better with busy personal, family, and work schedules.…”
Section: Discussionmentioning
confidence: 98%
“…The advancement of mobile information technology has facilitated businesses to employ diverse self-service technologies, expanding service channels and enhancing customer engagement, thereby revolutionizing the service landscape. Current self-service technology interfaces utilized by organizations encompass kiosks, the internet, interactive voice response, and mobile services (Oliveira et al, 2021). Human-technology interaction denotes the interaction between customers and self-service facilities.…”
Section: Interaction With Technology (Iwt)mentioning
confidence: 99%